2018
DOI: 10.26719/2018.24.11.1058
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of Caesarean delivery in Punjab, Pakistan

Abstract: especially in developing countries (5). As a reference, the World Health Organization, in its 1985 report, suggested an optimal range for C-section rates of 5-15% (6). Many studies have found that the likelihood of delivery through C-section depends on a number of institutional, demographic and socioeconomic factors. The availability of facilities, obstetricians and the place of birth, that is, private or public sector institutions, is associated with C-section rate (7,8). C-section is significantly associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
2
13
0
3
Order By: Relevance
“…There is increasing number of cesarean delivery worldwide with a rate of cesarean section is 32.7% in urban areas versus 19.7% in rural areas of Punjab. 1 Other authors have reported lower segment cesarean section (LSCS) rates to be as high as 44%. 2,3 The rising trend of cesarean section may help to prevent maternal and neonatal deaths from obstetric complication but it may increase the risk of infectious morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing number of cesarean delivery worldwide with a rate of cesarean section is 32.7% in urban areas versus 19.7% in rural areas of Punjab. 1 Other authors have reported lower segment cesarean section (LSCS) rates to be as high as 44%. 2,3 The rising trend of cesarean section may help to prevent maternal and neonatal deaths from obstetric complication but it may increase the risk of infectious morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The cesarean section rate should not rise above 10-15% 1 . According to WHO, Cesarean section rates have risen from 2.7% in 1990-91 to 15.8% in 2012-13 with around 9700 mortalities due to maternal complications in 2015 in Pakistan 2,3 . A significant rise of up to 40% has been seen in rich, educated and urban living ladies wishing for a reduced family size, avoidance of pain and unpredictability of normal labor and damage to pelvic floor.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to increase births attended by skilled health professionals often lead to birth in a health facility/hospital 3 . Attendants in health facilities can intervene in case of complications 4 .…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies investigating obstetric care in Pakistan 4,22,23 . The rate of caesarean section, indications for CS, different methods for induction, associated factors with ruptured uterus and severe perineal trauma are among central obstetric issues investigated 4,[22][23][24][25] . The majority of these studies were performed at university, public and teaching hospitals, or based on demographic health surveys 4,22,23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation